Prevalence and variables associated with insomnia among COVID-19 survivors in Colombia: Insomnia in COVID-19 survivors - Pedrozo-Pupo, John Carlos; Caballero-Domínguez, Carmen Cecilia; Campo-Arias, Adalberto (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work. The prevalence of insomnia is higher in COVID-19 survivors. However, there is little information about his associated variables. The aimed to know the prevalence and variables associated with insomnia among COVID-19 survivors in Colombian adults. Method. Three hundred and thirty COVID-19 survivors participated in a cross-sectional study. Insomnia was quantified with the Athens Insomnia Scale (cut-off score ≤ 6, Cronbach’s alpha of 0.90). Results. COVID-19 survivors were between 18 and 89 years (Mean = 47.7, SD = 15.2); the majority were women (61.5%), university-educated (62.4%), low income (71.2%), married or free union (66.1%), not healthcare workers (85.8%), without comorbidities (63.0%), asymptomatic or mild COVID-19 (66.1%), duration of COVID-19 symptoms in less than three weeks (80.0%) and remission of symptoms less two months by the day of study participation (73.0%). Scores on the Athens Insomnia Scale were observed between 0 and 24 (M = 7.3, SD = 5.1, Me = 7, IQR = 3 – 10), 60% presented insomnia. Insomnia was associated with post-traumatic stress symptoms (OR = 8.8, 95%CI 2.7 – 29.5), COVID-19 symptoms for more than three weeks (OR = 2.1, 95%CI 1.1 – 3.9), female gender (OR = 1.9, 95%CI 1.2 – 3.2) and married or free union marital status (OR = 1.8, 95%CI 1.1 – 3.0). Conclusion. The frequency of insomnia in COVID-19 survivors is high and mainly related to post-traumatic stress, symptoms of COVID-19 for more than three weeks, and the female gender. It is necessary to implement follow-up studies over time to evaluate the persistence of insomnia.